Harm reduction must be recognised an essential public health intervention during crises - Robert Csák; Sam Shirley-Beavan; Arielle Edelman McHenry; Colleen Daniels; Naomi Burke-Shyne (BMC, 2021)
Abstract The COVID-19 had a substantial impact on the provision of harm reduction services for people who use drugs globally. These front-line public health interventions serve a population that due to stigma, discrimination and criminalisation, faces barriers to accessing health and social services and are particularly vulnerable to public health crises. Despite this, the pandemic has seen many harm reduction services close, reduce operations or have their funding reduced. Simultaneously, around the world, harm reduction services have been forced to adapt, and in doing so have demonstrated resilience, flexibility and innovation. Governments must recognise the unique abilities of harm reduction services, particularly those led by the community, and identify them as essential health services that must be protected and strengthened in times of crisis.